MicroRNA, Proteins, and Metabolites as Novel Biomarkers for Prediabetes, Diabetes, and Related Complications - Vaishya, Suniti; Sarwade, Rucha D.; Seshadri, Vasudevan (Frontiers in Endocrinology, 2018)
Type 2 diabetes mellitus (T2DM) is no more a lifestyle disease of developed countries. It has emerged as a major health problem worldwide including developing countries. However, how diabetes could be detected at an early stage (Prediabetes) to prevent the progression of disease is still unclear. Currently used biomarkers like glycated haemoglobin and assessment of blood glucose level have their own limitations. These classical markers can be detected when the disease is already established. Prognosis of disease at early stages and prediction of population at higher risk require identification of specific markers that are sensitive enough to be detected at early stages of disease. Biomarkers which could predict the risk of disease in people will be useful for developing preventive/proactive therapies to those individuals who are at higher risk of developing the disease. Recent studies suggested that expression of biomolecules including; miRNAs, proteins and metabolites specifically change during progression of T2DM and related complications, suggestive of disease pathology. Owing to their omnipresence in body fluids and their association with onset, progression and pathogenesis of T2DM, these biomolecules can be potential biomarker for prognosis, diagnosis and management of disease. In this article, we summarize biomolecules that could be potential biomarkers and their signature changes associated with T2DM and related complications during disease pathogenesis.